Mixed Channel Traffic Grooming in an SBPP-Based IP Over MCF-EON with Minimized Inter-Core Crosstalk - Tang, Fengxian; Wang, Sunan; Shen, Gangxiang (2023 Asia Communications and Photonics Conference/2023 International Photonics and Optoelectronics Meetings (ACP/POEM), 2023)
Traffic grooming and shared backup path protection (SBPP) can significantly improve network resource utilization and ensure the survivability in multi-core fiber-elastic optical networks (MCF-EON). However, addressing routing, core, modulation, and spectrum assignment (RCMSA) with the consideration of inter-core crosstalk in such networks is challenging. In this paper, we propose an efficient auxiliary graph (AG) based algorithm to tackle this challenge in the context of an IP over MCF-EON. Our results demonstrate significant improvement in network resource utilization and reduction in inter-core crosstalk, thereby confirming the effectiveness of the proposed approach.